Vegetative compatibility and pathogenicity of Diplodia mutila isolates on oak - Ragazzi, A. (European journal of forest pathology, 1997)
Forty isolates of Diplodia mutila, a dieback agent on oaks were characterized by their capacity to produce heterokaryons, by their vegetative compatibility, and by their pathogenicity tests on Quercus cerris. The forty isolates were collected from Quercus cerris, Quercus frainetto, Quercus ilex, Quercus pubescens, Quercus robur and Quercus suber in different regions in Italy. Three nit mutants (nit,, nit, and nit,) were identified with different nitrogen sources: sodium nitrite, sodium nitrate, uric acid, ammonium tartrate and hypoxanthine. O n the two nutrient media employed, a potato dextrose agar (PDA) medium with chlorate (PDC), and a minimal agar medium with chlorate (MMC), isolates obtained from Q. cerris Felded the greatest number of mutants: 254 on PDC (out of a total of 583) and 190 on MMC (out o a total of 440). Nine vegetative compatibility grou s (VCGs) were identified. There was a strong association between these VCGs and host species. Alfisolates tested except one from Q. cerris were pathogenic.
Keywords: diplodia mutila; disease (voyant); nit mutants; Pathogenicity; Quercus; vegetative compatibility